CLINICAL EVALUATION OF THE STABILITY OF IMPLANTS PLACED AT DIFFERENT SUPRACRESTAL LEVELS - B. Alper GÜLTEKIN; Ali ŞIRALI; Pınar GÜLTEKIN; Selim ERSANLI (Istanbul University, 2016)
Purpose: The aim of this study was to evaluate the stability during healing and before loading of implants placed at two different supracrestal levels according to their collar texture. Materials and Methods: This retrospective study included patients who received posterior implants with the same macro design. Implants with a machined collar were placed 0.3 mm above the crestal bone (M group), while those with a laser-microtextured collar were placed 1 mm above the crestal bone (L group). All implants healed in a single stage with healing abutments. Implant stability quotient (ISQ) values were determined using resonance frequency analysis immediately after implant placement during surgery and after 1, 4, 8, and 12 weeks after surgery. Other evaluated factors for stability included the implant diameter and length and the site of placement (maxilla or mandible). Results: In total, 103 implants (47 L, 56 M) were evaluated. The median ISQ values at baseline and 1 week after placement were significantly higher for the M group than for the L group (p=0.006 and p=0.031, respectively). There were no differences at the subsequent observation points. The ISQ value was higher for wide-diameter than regular diameter (p=0.001) and mandibular implants than maxillary implants (p=0.001 at 0-8. weeks; p=0.012 at 12 weeks) at all observation points. When diameter data were neglected, the implant length did not influence the ISQ value at all observation points. Conclusion: Our results suggest that submerging implant more inside bone may only influence primary stability. Moreover, the implant diameter and site of placement influence primary and secondary stability before loading, whereas the implant length does not when its diameter is not accounted for.